(untitled) (Forum for Linguistic Studies, 2024)
The advent of Artificial Intelligence (AI) has significantly transformed forensic analysis, offering promising capabilities for the criminal justice system. This article explores the role of AI in forensic analysis, focusing on its application in various domains such as digital forensics, facial recognition, voice analysis, and pattern recognition. The paper delves into the challenges associated with the integration of AI technologies in forensic practices, particularly concerning the accuracy, transparency, and ethical implications of AI-driven evidence. It examines the legal admissibility of AI-generated forensic evidence in Indian courts, analysing existing laws and judicial precedents to evaluate their adequacy in addressing emerging technologies. By assessing the current legal frameworks and identifying potential gaps, the article aims to propose guidelines for ensuring that AI evidence is admissible, reliable, and justifiable within India’s legal system. This work seeks to contribute to the evolving discourse on the intersection of technology, law, and justice, advocating for the creation of a robust legal framework that can incorporate AI’s advancements while safeguarding legal rights and fairness.